2012
DOI: 10.1038/ejhg.2011.261
|View full text |Cite
|
Sign up to set email alerts
|

KIF1A missense mutations in SPG30, an autosomal recessive spastic paraplegia: distinct phenotypes according to the nature of the mutations

Abstract: The hereditary spastic paraplegias (HSPs) are a clinically and genetically heterogeneous group of neurodegenerative diseases characterised by progressive spasticity in the lower limbs. The nosology of autosomal recessive forms is complex as most mapped loci have been identified in only one or a few families and account for only a small percentage of patients. We used next-generation sequencing focused on the SPG30 chromosomal region on chromosome 2q37.3 in two patients from the original linked family. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 25 publications
5
113
1
1
Order By: Relevance
“…10 On the basis of structural analyses, the recessive variants c.764C4T (p. (Ala255Val)) and c.1048C4G (p.(Arg350Gly)) were predicted to disrupt the back door structure or the neck linker between the motor domain and cargo binding regions, respectively. 6,7,10 Functional testing by the expression of variants in rat hippocampal neurons suggested that the recessive variants impaired motor activity of KIF1A but to a lesser degree than the dominant disease variants. 10 Therefore, a less severe biochemical phenotype may explain why c.764C4T (p.(Ala255Val)) and c.1048C4G (p.(Arg350Gly)) are disease causing only in the homozygous state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 On the basis of structural analyses, the recessive variants c.764C4T (p. (Ala255Val)) and c.1048C4G (p.(Arg350Gly)) were predicted to disrupt the back door structure or the neck linker between the motor domain and cargo binding regions, respectively. 6,7,10 Functional testing by the expression of variants in rat hippocampal neurons suggested that the recessive variants impaired motor activity of KIF1A but to a lesser degree than the dominant disease variants. 10 Therefore, a less severe biochemical phenotype may explain why c.764C4T (p.(Ala255Val)) and c.1048C4G (p.(Arg350Gly)) are disease causing only in the homozygous state.…”
Section: Discussionmentioning
confidence: 99%
“…5 Next, homozygous missense variants in the KIF1A motor domain were found causative for the autosomal recessive hereditary spastic paraplegia (HSP) subtype SPG30. [6][7][8] HSP is characterized by the degeneration of axons of the corticospinal tract motor neurons. If additional symptoms or signs are present, the patient has 'complicated' rather than 'pure' HSP.…”
Section: Introductionmentioning
confidence: 99%
“…5 In family B, total RNA was isolated from peripheral blood lymphocytes and reverse transcribed to cDNA. The cDNA obtained was PCR-amplified using forward and reverse primers corresponding to cDNA positions c.124 and c.738 (NM_001143905.2) in exon 1 and exon 3, respectively.…”
Section: Patient Cohortmentioning
confidence: 99%
“…SPG30 is a rare ARHSP form with an age at onset between 10 and 39 years and a slow disease progression 84,85 . Cerebellar signs, or cerebellar atrophy and axonal sensorimotor peripheral neuropathy are frequently associated signs.…”
Section: Spg30 (Kif1a)mentioning
confidence: 99%